Perancangan Model Ontologi Untuk Tempat Wisata DiBali - Ni Wayan Anti Andari; I Wayan Supriana (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Bali is one of the many places that become a tourist destination for people who want to enjoy the beauty of nature and culture in their vacation. However, many tourists find it difficult to find information about tourist attractions in Bali. To overcome this we need a system that can help tourists to find information about tourist objects in Bali quickly and precisely using a semantic web knowledge base, namely ontology. Semantic web is a website update that has an automation goal that is able to understand the meaning or concept of the data and the relationship between the two, so that it will produce a web that is in accordance with the wishes of website visitors. This study aims to develop an ontology model that will be applied to the tourism domain in Bali. The development methodology used in building the ontology model is Ontology Development 101. The ontology design is developed using the protégé application and testing will be carried out by asking questions on the ontology model using SPARQL. This ontology model is expected to be able to provide information related to application metadata based on semantic webs on tourist attractions on the island of Bali.